Qualification testing of welders - fusion welding : - International Organization for Standardization
This part of ISO 9606 specifies the requirements for qualification testing of welders for fusion welding of steels. It provides a set of technical rules for a systematic qualification test of the welder, and enables such qualifications to be uniformly accepted independently of the type of product, location and examiner or examining body